Measles Surveillance in Pekanbaru, Indonesia: An Evaluation Study (2022–2025) - Maser, Silvia Elsih; Zaman, Kamali; Susanti, Melly (Jurnal Epidemiologi Kesehatan Komunitas, 2026)
Background: Measles cases in Pekanbaru City fluctuated and increased during 2022–2025, with an outbreak occurring in 2025. This situation is associated with low immunization coverage and suboptimal implementation of Case-Based Measles Surveillance (CBMS). This study aimed to identify gaps in measles surveillance implementation, prioritize problems, and formulate recommendations using fishbone analysis and a Plan of Action (POA).Methods: This exploratory qualitative study was conducted in October 2025. Informants were selected using purposive sampling, consisting of 4 informants: 2 main informants, namely VPD surveillance officers and Early Warning and Response System (EWRS) officers, as well as 2 supporting informants, namely an epidemiologist and an immunization program manager. Data were collected through in-depth interviews, observation, and document review, with data validity ensured through triangulation (source, data, and method triangulation). Qualitative analysis was followed by fishbone analysis and the development of a Plan of Action (POA).Result: CBMS implementation reached only 48%, indicating suboptimal surveillance performance despite adequate data quality and relevance. Barriers to CBMS implementation involved human resources, funding, methods, infrastructure, and environmental factors. Proposed solutions included strengthening workforce capacity and numbers, optimizing budgets through activity integration, improving supervision and reporting systems, enhancing laboratory facilities, increasing immunization coverage, and reinforcing community-based surveillance.Conclusion: A targeted POA is required to strengthen human resources, ensure budget availability, improve data recording and reporting quality, fulfill CBMS supporting facilities, and increase measles–rubella immunization coverage to enhance measles surveillance effectiveness and interrupt transmission in Pekanbaru City.